Properties of optical and photovoltaic cells on the base of In4Se3, In4(Se3)1-х(Te3)х crystals - Стребежев, Володимир Вікторович; Стребежев, Віктор Миколайович; Нічий, Сергій Васильович; Юрійчук, Іван Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
Theoretical calculations of thin-film interference systems for design of IR-filters on the base of In4(Se3)1-xTe3x solid solution crystals are carried out. Interference-absorptive band-pass filters on In4(Se3)1-xTe3x crystal with different cutting wavelength position depending on the composition x of the solid solution are produced by vacuum evaporation. Spectral transmission characteristics of the filters and dependence of their parameters on structural perfection of substrates and filter films are studied. Photosensitive elements on the base of In4(Se3)1-xTe3x homo-epitaxial heterojunctions are designed and laser correction of their photosensitivity spectral characteristics is carried out. Surface morphology of epitaxial layers is studied by electron raster microscopy. Temperature dependence of In4(Se3)1-xTe3x based photosensitive elements is measured. Mechanical strength and stability of filters and photosensitive elements spectral characteristics under cooling are studied. Laser treatment of photosensitive elements significantly increases photo-response signal of epitaxial structures at optimal operating temperatures.